Pengaruh Struktur Pendapatan terhadap Risiko Bisnis Perbankan Syariah di Indonesia - Maula, Kholida Atiyatul (UI Scholars Hub, 2015)
The purpose of this study was to analyze the effect of the income structure of Islamic banking to Islamic banking business risk in Indonesia. The results showed that the average level of business risk in Indonesia with 11 samples of Islamic banking are listed on the Stock Exchange in 2011 to 2013, shows the average value of 7.49% with a range of 1% to 23.5% with a standard value his deviation of 7.7%. Islamic banking is expected to minimize the risk of the business in order to survive and be able to provide financial facilities with financial instruments (Financial Instruments), which conformed to the rules and norms of Shariah Furthermore, the results confirm that mudaraba and ijaroh significant influence on business risk while variable musharaka and murabaha, no significant effect to business risk.